Nano-ceramic synergistic modified Al-Si alloy primary silicon refining method based on laser additive manufacturing
By adding TiB2 and Al2O3 nanoceramic powders to high Si content Al-Si alloys and using laser powder bed melting technology, the problems of strength and plasticity reduction caused by the coarseness of primary silicon in Al-Si alloys are solved, and the refinement of primary silicon and the improvement of material mechanical properties are achieved.
Patent Information
- Application Number
- CN202411761601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Coarse primary silicon in high Si content Al-Si alloys reduces the strength and plasticity of the material, and the laser powder bed melting process has limited effect in refining primary silicon.
By adding TiB2 and Al2O3 nanoceramic powders to the Al-Si alloy, nanoceramic particle-enhanced Al-Si alloy composites are prepared using laser powder bed melting technology to promote the nucleation and refinement of primary silicon.
The size and morphology of primary silicon in Al-Si alloys are significantly refined, and the mechanical properties of the material are improved, including the improvement of compressive strength.
Smart Images

Figure CN119703123A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of Al-Si alloy materials, and in particular relates to a method for refining primary silicon of Al-Si alloy synergistically modified by nano-ceramics based on laser additive manufacturing. Background Art
[0002] Al-Si alloys with silicon content exceeding 22 wt.% belong to high-silicon aluminum alloys. This type of aluminum alloy has excellent thermal stability and wear resistance, and has good development prospects in transportation, power machinery, portable electronic product device packaging, and sealed packaging in high-end fields. However, coarse primary silicon in the microstructure of high-Si content Al-Si alloys will reduce the strength and plasticity of aluminum alloy materials, thereby deteriorating the performance of Al-Si alloys. Therefore, refining primary silicon in high-Si content Al-Si alloys and improving their micromorphology are necessary means to improve the comprehensive performance of high-Si content Al-Si aluminum alloys. Compared with conventional casting, the preparation of Al-Si alloys using laser powder bed fusion technology has incomparable advantages. Laser powder bed melting is a non-steady-state solidification process, which can increase the heat dissipation of the melt during solidification, thereby increasing the cooling rate and supercooling, shortening the crystal growth time, and achieving the purpose of grain refinement. Therefore, the laser powder bed melting process can refine the primary silicon phase and matrix grains in the microstructure of high-Si content Al-Si alloys, and thus has potential in the preparation of high-Si content Al-Si alloys with excellent performance. However, the degree of refinement of primary silicon in high-Si content Al-Si alloys formed by laser powder bed melting is limited, and the primary silicon morphology in the microstructure of Al-Si alloy laser powder bed melting parts still has sharp edges and obvious corners, which will also have an adverse effect on the mechanical properties of the material. Therefore, by adding nucleating agents or modifiers to high-Si content Al-Si alloys, the heterogeneous nucleation cores of primary silicon are increased, and the continuous growth of primary silicon is inhibited to improve the microstructure and distribution state of primary silicon, thereby improving the mechanical properties of the material. This method is not limited by production process and production scale, and its application prospects are relatively broad.
[0003] According to solidification theory, the formation of primary silicon includes two processes: nucleation and growth. Phase fluctuation is the basis for the generation of crystal nuclei. In the original high-Si content Al-Si alloy, the formation of silicon phase nuclei mainly comes from the Si-Si atomic clusters frozen in the supercooled melt. The large-sized Si-Si atomic clusters that meet the critical nucleus formation conditions can become stable cores, and some Si atomic clusters will be redissolved in the aluminum melt through Si atomic diffusion. The silicon phase growth process is mainly achieved by the continuous migration of Si atoms in the melt to the surface of the Si-Si atomic clusters and the continuous advancement of the liquid-solid interface. During the solidification process of aluminum alloys, Si atoms diffuse faster than Al atoms, and due to energy differences, the diffusion rates of Si atoms on crystal planes with different crystal indexes are different. Atoms on high crystal plane index planes diffuse faster than those on low crystal plane index planes. Primary silicon is always on the twin plane {111} along the surface. <112> or <110> Directional nucleation occurs and the silicon crystal preferentially grows in a small plane growth mode. Atomic dislocation is inevitable during crystal growth, which changes the growth direction of the silicon crystal. Therefore, the primary silicon phase is polygonal and multi-faceted. Under the microscope, its morphology is irregular polygonal or petal-shaped, which affects the mechanical properties of the Al-Si alloy. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for refining primary silicon in Al-Si alloy by synergistic modification of nano-ceramics based on laser additive manufacturing, in order to significantly improve the mechanical properties of Al-Si alloy.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for refining primary silicon in a nano-ceramic-modified Al-Si alloy based on laser additive manufacturing comprises the following steps: (1) dispersing TiB2 nano-ceramic powder and Al2O3 nano-ceramic powder in anhydrous ethanol, and then drying to obtain a uniformly dispersed mixed nano-ceramic powder; (2) mixing the Al-Si alloy powder and the mixed nano-ceramic powder in step (1) uniformly to obtain a nano-ceramic particle reinforced Al-Si alloy composite powder; (3) Establish a 3D solid geometric model of the target part, then slice the model and plan the laser scanning path, discretize the 3D solid into a series of 2D data, save the file and import it into the laser powder bed fusion forming equipment; (4) The laser powder bed fusion forming equipment melts the nano-ceramic particle reinforced Al-Si alloy composite powder in step (2) layer by layer according to the file saved in step (3), and finally forms the target part to be built.
[0006] Specifically, in step (1), the TiB2 nano-ceramic powder used is an irregular TiB2 ceramic powder with a purity greater than 99.9% and a particle size distribution range of 30 to 75 nm.
[0007] Specifically, in step (1), the Al2O3 nano-ceramic powder used is an irregular Al2O3 ceramic powder with a purity greater than 99.9% and a particle size distribution range of 25 to 60 nm.
[0008] Preferably, in step (1), the mass ratio of TiB2 ceramic powder to Al2O3 ceramic powder is 3:1 to 3:2. If the content of nano-ceramic particles is too low, the refinement effect of primary silicon in the Al-Si alloy is poor; if the content of nano-ceramic particles is too high, the metallurgical defects in the Al-Si alloy structure increase, the laser forming quality decreases, and the performance of the composite material is affected.
[0009] Specifically, in step (1), TiB2 ceramic powder and Al2O3 ceramic powder are dispersed in anhydrous ethanol according to a solute: solvent mass ratio of 10: (1-2), placed in an ultrasonic oscillator for oscillation treatment, and then the resulting mixed solution is placed in a vacuum drying oven for drying treatment to obtain uniformly dispersed nano-ceramic powder; the ultrasonic power of the ultrasonic oscillator is 1000-1200W, and the ultrasonic oscillation time is 8-12h; the drying temperature of the vacuum drying oven is 70-90°C, and the drying time is 10-14h.
[0010] Specifically, in step (2), the Al-Si alloy powder has a particle size distribution range of 20-48 μm, a silicon content of 22-55 wt.%, an iron content of 0.08-0.17%, a copper content of 2.3-3.0%, and the balance is aluminum.
[0011] Preferably, in step (2), the mixed nano-ceramic powder accounts for 1.5 to 6 wt.% of the mass of the Al-Si alloy powder.
[0012] Preferably, in step (2), the Al-Si alloy powder and the mixed nano-ceramic powder are uniformly mixed by a QM series planetary ball mill under the protection of inert gas. The process uses a ceramic jar, and the ball milling medium is a ceramic grinding ball with a diameter of 6 mm and 8 mm. The ball milling process parameters are set as follows: the ball-to-material ratio is 2:1; at the same time, in order to prevent the temperature in the ball mill from being too high, the equipment operation mode is selected as the interval type during ball milling, the speed is 150-250 rpm, the ball milling time is 3-5 h, the ball milling time is 14-20 min each time, and the interval time is 4-6 min.
[0013] Specifically, in step (4), the laser power used by the laser powder bed fusion forming equipment is 350-450 W, the scanning speed is 1600-2400 mm / s, the scanning interval is 40-60 μm, the powder thickness is 40-60 μm, and a partitioned island scanning strategy is adopted.
[0014] Preferably, the laser powder bed fusion forming equipment uses an SLM-150 laser powder bed fusion forming equipment, which mainly includes a YLR-500 fiber laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system, and a cooling circulation system. Before forming, the sandblasted aluminum substrate is fixed on the workbench of the laser powder bed fusion forming equipment and leveled, and then the forming chamber is sealed, evacuated, and an inert gas protective atmosphere is introduced through a sealing device. The typical laser powder bed fusion forming process is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to a pre-designed scanning path, so that the powder layer undergoes rapid melting and solidification, thereby obtaining the first two-dimensional plane of the part; (b) The computer control system causes the forming substrate to drop a powder layer thickness, and conversely, causes the powder supply cylinder piston to rise a powder layer thickness, and the powder spreading device re-lays a layer of powder to be processed, and the laser beam completes the second powder layer scanning according to the slicing information to obtain the second two-dimensional plane of the part; (c) Repeat the above steps, and the powder to be processed is formed layer by layer until the part is processed. In step (4), the laser powder bed melting parameters are determined after process optimization. Beneficial Effects
[0015] (1) In the present invention, the nucleation and growth process of primary silicon in the nano-ceramic particle reinforced Al-Si alloy microstructure is different from the above. When there is a good interface coherence relationship between the two phases, one of the phases can serve as the core of the heterogeneous nucleation of the other phase, and when the lattice mismatch between the two crystal forms is less than 6%, the heterogeneous nucleation can be effectively promoted. Si has a face-centered cubic structure with a lattice constant of 0.54 nm, and Al2O3 has a cubic crystal structure with a lattice constant of 0.79 nm. Si and Al2O3 have similar crystal structures and a lattice mismatch of 3%. The Al2O3 phase can serve as a suitable substrate for the heterogeneous nucleation of primary silicon, promote the nucleation of the primary silicon phase, increase its nucleation rate, and achieve the effect of refining the size of the primary silicon. TiB2 nano-ceramic particles are located at the solid-liquid interface of the aluminum alloy melt, which can prevent the diffusion and aggregation of Si atoms to Si-Si atomic clusters to a certain extent, resulting in anisotropic changes in primary silicon and inhibiting the growth of silicon phase, thereby regularizing the morphology of primary silicon and refining its size, while refining the matrix grains. Therefore, adding an appropriate amount of TiB2+Al2O3 nano-ceramic phase to the Al-Si alloy can refine the matrix grains and primary silicon phase, and adjust the morphology and distribution state of its hard and brittle Si phase. The combined effect of the two nano-ceramic particles can significantly improve the mechanical properties of Al-Si alloys with high Si content.
[0016] (2) In the present invention, the nano-ceramic particles and Al-Si alloy powder are mixed and placed in a QM series planetary ball mill for ball milling and mixing. By optimizing the ball milling process, nano-ceramic particles are uniformly distributed, have good flow properties, and are suitable for laser powder bed melting to obtain nano-ceramic particle reinforced Al-Si alloy composite powders. The process is simple to operate and saves costs.
[0017] (3) In the present invention, compared with Al-Si alloy powder, the laser absorption rate of the composite powder is significantly increased after adding an appropriate amount of nano-ceramic particles to the Al-Si alloy. During the laser powder bed fusion forming process, the laser energy input of the powder bed is increased, so that the powder layer can be fully melted, thereby improving the forming quality and mechanical properties of the parts.
[0018] (4) The present invention uses laser powder bed fusion technology to prepare Al-Si alloy materials, which not only shortens the production cycle and improves product production efficiency, but also can form parts with complex geometric shapes without subsequent machining. The cooling rate of the molten pool during laser powder bed fusion is extremely high, reaching 10 3 ~10 8 K / s, which increases the supercooling of the Al-Si alloy melt, avoids the formation of coarse dendrites in traditional processing technology, and improves the mechanical properties of parts.
[0019] (5) In the present invention, Si and Al2O3 have similar crystal structures and have a good interfacial coherence relationship. Al2O3 particles can act as heterogeneous nucleation sites for primary silicon, thereby increasing the nucleation rate of primary silicon and refining the size of primary silicon. TiB2 nanoparticles are distributed on the solid-liquid interface, which can prevent Si atoms from diffusing and aggregating to Si-Si atomic clusters to a certain extent, thereby inhibiting the growth of silicon phase and promoting the regularization of primary silicon morphology and refinement of size. Therefore, adding an appropriate amount of Al2O3 and TiB2 nanoceramic phases to Al-Si alloys can refine primary silicon and adjust its morphology and distribution state, significantly improving the mechanical properties of Al-Si alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0021] Figure 1 This is the cross-sectional organization diagram of the (TiB2+Al2O3) / Al-Si composite powder in Example 1.
[0022] Figure 2 This is a physical photo of the laser powder bed fusion (TiB2+Al2O3) / Al-Si composite material sample in Example 1.
[0023] Figure 3 This is the cross-sectional OM image of the laser powder bed melted (TiB2+Al2O3) / Al-Si composite material sample in Example 1.
[0024] Figure 4 This is the cross-sectional OM image of the laser powder bed melted (TiB2+Al2O3) / Al-Si composite material in Example 2.
[0025] Figure 5 This is the cross-sectional OM image of the laser powder bed melted Al-Si alloy sample in Comparative Example 1. DETAILED DESCRIPTION
[0026] The present invention can be better understood with reference to the following examples.
[0027] In the following examples, the raw materials used are irregular Al2O3 ceramic powder, with a particle size distribution range of 25~60nm and a purity greater than 99.9%. Irregular TiB2 ceramic powder, with a particle size distribution range of 30~75 nm and a purity greater than 99.9%. Al-Si alloy powder has a particle size distribution range of 20~48 μm, wherein the silicon content is 22~55 wt.%, the iron content is 0.08~0.17%, the copper content is 2.3~3.0%, and the balance is aluminum. Example 1
[0028] (1) TiB2 and Al2O3 with a mass ratio of 3:1 were dispersed in anhydrous ethanol according to a solute:solvent mass ratio of 10:1, and placed in an ultrasonic oscillator for oscillation treatment. The ultrasonic power was 1000 W and the ultrasonic oscillation time was 10 h. Then the mixed solution was placed in a vacuum drying oven for drying treatment. The drying temperature was 80 °C and the drying time was 12 h to obtain uniformly dispersed nanoceramics. The ceramic powder was mixed with Al-Si alloy powder at a ratio of 1.5 wt.% to prepare a composite powder. The ball milling and mixing operation was carried out in a QM series planetary ball mill. The process used a ceramic jar and the ball milling media were ceramic grinding balls with diameters of 6 mm and 8 mm. The ball milling process parameters were set as follows: ball-to-material ratio of 2:1, ball milling speed of 150 rpm, and ball milling time of 5 h. At the same time, in order to prevent the temperature in the ball mill jar from being too high, the equipment operation mode was selected as the interval type during ball milling, that is, the equipment was suspended for air cooling for 5 min after running for 15 min. The ball milling process is required to be carried out under argon protection to prevent the aluminum alloy powder from being oxidized or contaminated. The cross-sectional microstructure of the (TiB2+Al2O3) / Al-Si composite powder prepared in this embodiment is shown in FIG. Figure 1 shown.
[0029] (2) Target part modeling and slicing The 3D solid geometric model of the target part was established using Soildworks software in the computer, and then the 3D solid model was sliced and scanned using Magics software. The 3D solid was discretized into a series of 2D data, and the file was saved and imported into the laser powder bed fusion forming equipment. The laser process parameters were set as follows: laser power of 350 W, laser scanning speed of 1600 mm / s, scanning spacing of 50 μm, powder thickness of 50 μm, partitioned island scanning strategy, and the rotation angle of the laser scanning direction of adjacent layers was 37°.
[0030] (3) Laser powder bed fusion forming process The nano-ceramic particle reinforced Al-Si alloy composite powder obtained in step (1) is used for laser powder bed fusion forming. The SLM-150 laser powder bed fusion equipment is used, and the system mainly includes a YLR-500 fiber laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system and a cooling circulation system. Before forming, the sandblasted aluminum substrate is fixed on the workbench of the laser powder bed fusion forming equipment and leveled, and then the forming cavity is sealed by a sealing device, evacuated and an argon protective atmosphere is introduced. The typical laser powder bed fusion forming process is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to the pre-designed scanning path, causing the powder layer to melt and solidify rapidly, thereby obtaining the first two-dimensional plane of the part; (b) The computer control system causes the forming substrate to drop by one powder layer thickness, and conversely, causes the piston of the powder supply cylinder to rise by one powder layer thickness. The powder spreading device re-spreads a layer of powder to be processed, and the laser beam completes the second powder layer scan according to the slicing information to obtain the second two-dimensional plane of the part; (c) Repeat the above steps, and the powder to be processed is formed layer by layer until the part is processed.
[0031] After cooling, take the formed substrate out of the equipment (such as Figure 2 As shown in Figure 2, the parts were separated from the substrate using a wire cutting process to obtain a (TiB2+Al2O3) / Al-Si composite material sample. The (TiB2+Al2O3) / Al-Si composite material block sample was ground, polished and etched according to the standard metallographic sample preparation method. It was found that the primary silicon was significantly refined after the addition of the nano-ceramic reinforcement phase, and the large-sized snowflake-shaped primary silicon in the coarse-grained area was significantly reduced or even disappeared. The morphology of the primary silicon changed from snowflake to polygonal or irregular, and the average size was reduced to about 6.58 μm, which was a 27% decrease in average size. However, the morphology of the block primary silicon in the fine-grained area of the nano-ceramic modified Al-Si alloy did not change significantly, and the average size was about 2.14 μm, see Figure 3 The obtained (TiB2+Al2O3) / Al-Si composite material standard compression specimen was subjected to room temperature compression test, and its compressive strength could reach 741MPa, which was 21% higher than that of Al-Si alloy without ceramic reinforcement phase. Example 2
[0032] (1) TiB2 and Al2O3 with a mass ratio of 2:1 were dispersed in anhydrous ethanol according to a solute:solvent mass ratio of 10:1, and placed in an ultrasonic oscillator for oscillation treatment. The ultrasonic power was 1000 W and the ultrasonic oscillation time was 10 h. Then the mixed solution was placed in a vacuum drying oven for drying treatment. The drying temperature was 80 °C and the drying time was 12 h to obtain uniformly dispersed nanoceramics. The ceramic powder was mixed with Al-Si alloy powder at a ratio of 3.5 wt.% to prepare a composite powder. The ball milling and mixing operation was carried out in a QM series planetary ball mill. The process used a ceramic jar and the ball milling media were ceramic grinding balls with diameters of 6 mm and 8 mm. The ball milling process parameters were set as follows: ball-to-material ratio of 2:1, ball milling speed of 200 rpm, and ball milling time of 4 h. At the same time, in order to prevent the temperature in the ball mill jar from being too high, the equipment operation mode was selected as the interval type during ball milling, that is, the equipment was suspended for air cooling for 5 min after running for 15 min. The ball milling process is required to be carried out under argon protection to prevent the aluminum alloy powder from being oxidized or contaminated.
[0033] (2) Target part modeling and slicing The 3D solid geometric model of the target part was established using Soildworks software in the computer, and then the 3D solid model was sliced and scanned using Magics software. The 3D solid was discretized into a series of 2D data, and the file was saved and imported into the laser powder bed fusion forming equipment. The laser process parameters were set as follows: laser power of 450 W, laser scanning speed of 2400 mm / s, scanning spacing of 50 μm, powder thickness of 50 μm, partitioned island scanning strategy, and the rotation angle of the laser scanning direction of adjacent layers was 37°.
[0034] (3) Laser powder bed fusion forming process The nano-ceramic particle reinforced Al-Si alloy composite powder obtained in step (1) is used for laser powder bed fusion forming. The SLM-150 laser powder bed fusion equipment is used, and the system mainly includes a YLR-500 fiber laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system and a cooling circulation system. Before forming, the sandblasted aluminum substrate is fixed on the workbench of the laser powder bed fusion forming equipment and leveled, and then the forming cavity is sealed by a sealing device, evacuated and an argon protective atmosphere is introduced. The laser powder bed fusion forming process is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to the pre-designed scanning path, causing the powder layer to melt and solidify rapidly, thereby obtaining the first two-dimensional plane of the part; (b) The computer control system causes the forming substrate to drop by one powder layer thickness, and conversely, causes the piston of the powder supply cylinder to rise by one powder layer thickness. The powder spreading device re-spreads a layer of powder to be processed, and the laser beam completes the second powder layer scan according to the slicing information to obtain the second two-dimensional plane of the part; (c) Repeat the above steps, and the powder to be processed is formed layer by layer until the part is processed.
[0035] After cooling, the formed substrate is taken out of the equipment, and the parts are separated from the substrate by wire cutting process to obtain the (TiB2+Al2O3) / Al-Si composite material sample. The (TiB2+Al2O3) / Al-Si composite material block sample is ground, polished and corroded according to the standard metallographic sample preparation method. After adding the nano-ceramic reinforcement phase, the refinement effect of the primary silicon is significant. The large-sized snowflake-shaped primary silicon that was originally obviously present in the coarse-grained area is basically eliminated, and its morphology changes from the original snowflake shape to polygonal, and the average size is greatly reduced to ~6.43 μm, which is 29% smaller than the size of primary silicon in the alloy. In the fine-grained area, the morphology of the block primary silicon of the nano-ceramic modified Al-Si alloy remains basically unchanged, with an average size of about 2.20 μm, and no significant changes are observed, see Figure 4 The obtained (TiB2+Al2O3) / Al-Si composite material standard compression specimen was subjected to room temperature compression test, and its compressive strength can reach 755 MPa, which is 23% higher than that of Al-Si alloy without adding ceramic reinforcement phase. Example 3
[0036] (1) TiB2 and Al2O3 with a mass ratio of 3:2 were dispersed in anhydrous ethanol according to a solute:solvent mass ratio of 10:1, and placed in an ultrasonic oscillator for oscillation treatment. The ultrasonic power was 1000 W and the ultrasonic oscillation time was 10 h. Then the mixed solution was placed in a vacuum drying oven for drying treatment. The drying temperature was 80 °C and the drying time was 12 h to obtain uniformly dispersed nanoceramics. The ceramic powder was mixed with Al-Si alloy powder at a ratio of 6 wt.% to prepare a composite powder. The ball milling and mixing operation was carried out in a QM series planetary ball mill. The process used a ceramic jar and the ball milling media were ceramic grinding balls with diameters of 6 mm and 8 mm. The ball milling process parameters were set as follows: ball-to-material ratio of 2:1, ball milling speed of 250 rpm, and ball milling time of 3 h. At the same time, in order to prevent the temperature in the ball mill jar from being too high, the equipment operation mode was selected as the interval type during ball milling, that is, the equipment was suspended for air cooling for 5 min after running for 15 min. The ball milling process is required to be carried out under argon protection to prevent the aluminum alloy powder from being oxidized or contaminated.
[0037] (2) Target part modeling and slicing The 3D solid geometric model of the target part was established using Soildworks software in the computer, and then the 3D solid model was sliced and scanned using Magics software. The 3D solid was discretized into a series of 2D data, and the file was saved and imported into the laser powder bed fusion forming equipment. The laser process parameters were set as follows: laser power of 400 W, laser scanning speed of 2000 mm / s, scanning spacing of 50 μm, powder thickness of 50 μm, partitioned island scanning strategy, and the rotation angle of the laser scanning direction of adjacent layers was 37°.
[0038] (3) Laser powder bed fusion forming process The nano-ceramic particle reinforced Al-Si alloy composite powder obtained in step (1) is used for laser powder bed fusion forming. The SLM-150 laser powder bed fusion equipment is used, and the system mainly includes a YLR-500 fiber laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system and a cooling circulation system. Before forming, the sandblasted aluminum substrate is fixed on the workbench of the laser powder bed fusion forming equipment and leveled, and then the forming cavity is sealed by a sealing device, evacuated and an argon protective atmosphere is introduced. The laser powder bed fusion forming process is as follows: (a) The powder spreading device evenly spreads the powder to be processed on the forming substrate, and the laser beam scans the slicing area line by line according to the pre-designed scanning path, causing the powder layer to melt and solidify rapidly, thereby obtaining the first two-dimensional plane of the part; (b) The computer control system causes the forming substrate to drop by one powder layer thickness, and conversely, causes the piston of the powder supply cylinder to rise by one powder layer thickness. The powder spreading device re-spreads a layer of powder to be processed, and the laser beam completes the second powder layer scan according to the slicing information to obtain the second two-dimensional plane of the part; (c) Repeat the above steps, and the powder to be processed is formed layer by layer until the part is processed.
[0039] After cooling, the formed substrate was taken out of the equipment, and the parts were separated from the substrate by wire cutting process to obtain the (TiB2+Al2O3) / Al-Si composite material sample. The (TiB2+Al2O3) / Al-Si composite material block sample was ground, polished and corroded according to the standard metallographic sample preparation method. After adding nano-ceramic reinforcement phase, the microstructure of primary silicon changed significantly. The primary silicon in the coarse grain area changed significantly, and the large-size primary silicon was greatly reduced or even completely disappeared. Its morphology changed from complex snowflake shape to irregular shape, and the average size dropped sharply to ~6.60 μm, which was 27% lower than that of Al-Si without addition. The standard compression sample of the (TiB2+Al2O3) / Al-Si composite material was subjected to room temperature compression test, and its compressive strength could reach 735 MPa, which was 20% higher than that of Al-Si alloy without ceramic reinforcement phase. Comparative Example 1
[0040] The specific steps of this comparative example are basically the same as those of Example 1, except that: in step (1) of this comparative example, nano-ceramic powder is not added to the Al-Si alloy and the composite powder is not prepared by ball milling. Instead, a nearly spherical Al-Si alloy powder prepared by gas atomization is used as the raw material for laser powder bed melting forming. The microstructure is as follows: Figure 5 As shown. Figure 3 and Figure 5It can be found that the primary silicon in the coarse-grained area of the Al-Si alloy is in the shape of snowflakes with an average size of ~9.02 μm, and the average size of the blocky primary silicon in the fine-grained area is ~2.86 μm. The standard compression specimen of the Al-Si alloy obtained was subjected to a room temperature compression test, and its compressive strength was 612 MPa. Comparative Example 2
[0041] The specific steps of this comparative example are basically the same as those of Example 1, except that: in step (1) of this comparative example, only Al2O3 nano-ceramic powder is added to the Al-Si alloy to prepare a composite powder, and laser powder bed melting forming is performed. It is found that the refinement effect of primary silicon in the laser formed sample is not obvious, and large-sized snowflake-shaped primary silicon still exists in the coarse-grained area, with an average size of ~8.94 μm. In the fine-grained area, the morphology of the blocky primary silicon of the nano-ceramic modified Al-Si alloy remains basically unchanged, with an average size of ~2.78 μm, and no significant changes are observed. The standard compression sample of the Al2O3 / Al-Si composite material obtained was subjected to a room temperature compression test, and its compressive strength reached 627 MPa, which is an improvement compared to the Al-Si alloy without the addition of nano-ceramic reinforcement phase, but the improvement is not obvious. Comparative Example 3
[0042] The specific steps of this comparative example are basically the same as those of Example 1, except that: in step (1) of this comparative example, TiB2+Al2O3 nano-ceramics with a content of less than 1 wt.% are added to the Al-Si alloy to prepare a composite powder, and laser powder bed melting forming is performed. It is found that the refinement effect of primary silicon in the coarse grain area of the laser formed sample is not obvious, and a large amount of large-sized primary silicon still exists, with an average size of ~9.01 μm. The morphology of primary silicon in the fine grain area is almost unchanged, and the average size is still maintained at ~2.80 μm. The obtained (TiB2+Al2O3) / Al-Si composite material standard compression sample is subjected to room temperature compression test, and its compressive strength is 618MPa, which is not significantly changed compared with the compressive strength of Al-Si alloy without adding ceramic reinforcement phase. This is because the content of added nano-ceramics is too low, and the refinement effect of coarse primary silicon and matrix is not significantly improved, so the performance does not change significantly. Comparative Example 4
[0043] The specific steps of this comparative example are basically the same as those of Example 1, except that: in step (1) of this comparative example, a TiB2+Al2O3 nano-ceramic content higher than 10 wt.% is added to the Al-Si alloy to prepare a composite powder, and laser powder bed melting is performed. It is found that after adding the nano-ceramic reinforcement phase, the refinement effect of the primary silicon is significant. The large-sized snowflake-shaped primary silicon originally formed in the coarse-grained region is basically eliminated, and its morphology changes from the original snowflake shape to an irregular shape, and the average size is reduced to ~6.18 μm, which is 31% less than the size of the primary silicon in the alloy. In the fine-grained region, the morphology of the blocky primary silicon of the nano-ceramic modified Al-Si alloy remains basically unchanged, with an average size of about 2.05 μm. The obtained (TiB2+Al2O3) / Al-Si composite material standard compression specimen was subjected to room temperature compression test, and its compressive strength was only 523 MPa, which was 15% lower than that of Al-Si alloy without adding ceramic reinforcement phase. The compression performance was significantly reduced. This was because the nano-ceramic content was too high and the brittleness of the laser-formed sample increased. During the compression test, the sample fractured and failed prematurely, resulting in low mechanical properties.
[0044] It can be seen from Examples 1 to 3 and the comparative example that laser powder bed fusion forming (TiB2+ Al2O3) / AlSi 40 The compressive strength of the composite material sample is significantly increased, and the mechanical properties are significantly improved. Si and Al2O3 have similar crystal structures and have a good interface coherence relationship. Al2O3 particles can be quickly captured and absorbed by Si atomic clusters, thereby increasing the Al2O3 particle content inside the Si grains. When the nano-ceramic reinforced Al-Si alloy melt solidifies in the method of the present invention, the TiB2 nano-ceramic particles are located on the solid-liquid interface of the aluminum alloy melt, which can prevent the diffusion and aggregation of Si atoms to the Si-Si atomic clusters to a certain extent, resulting in anisotropic changes in primary silicon and inhibiting the growth of silicon phases, thereby regularizing the morphology of primary silicon and refining its size; Al2O3 particles act as heterogeneous nucleation points of primary silicon, increasing the nucleation rate of primary silicon and refining the size of primary silicon, so that the nano-ceramic particles can effectively improve the morphology of primary silicon in the Al-Si alloy composite tissue and fully refine the primary silicon distributed in the aluminum matrix.
[0045] The present invention provides a method and idea for the refinement of primary silicon in Al-Si alloys using nano-ceramics in collaboration with modified Al-Si alloys based on laser additive manufacturing. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be considered as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A method for refining primary silicon in nano-ceramic-modified Al-Si alloy based on laser additive manufacturing, characterized in that: The steps include: (1) dispersing TiB2 nano-ceramic powder and Al2O3 nano-ceramic powder in anhydrous ethanol, and then drying to obtain a uniformly dispersed mixed nano-ceramic powder; (2) mixing the Al-Si alloy powder and the mixed nano-ceramic powder obtained in step (1) uniformly to obtain a nano-ceramic particle reinforced Al-Si alloy composite powder; (3) Establish a 3D solid geometric model of the target part, then slice the model and plan the laser scanning path, discretize the 3D solid into a series of 2D data, save the file and import it into the laser powder bed fusion forming equipment; (4) The laser powder bed fusion forming equipment melts the nano-ceramic particle reinforced Al-Si alloy composite powder in step (2) layer by layer according to the file saved in step (3), and finally forms the target part to be built.
2. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (1), the TiB2 nano-ceramic powder used is an irregular TiB2 ceramic powder with a purity greater than 99.9% and a particle size distribution range of 30 to 75 nm.
3. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (1), the Al2O3 nano-ceramic powder used is an irregular Al2O3 ceramic powder with a purity greater than 99.9% and a particle size distribution range of 25 to 60 nm.
4. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (1), the mass ratio of TiB2 ceramic powder to Al2O3 ceramic powder is 3:1~3:
2.
5. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (1), TiB2 ceramic powder and Al2O3 ceramic powder are dispersed in anhydrous ethanol according to a solute: solvent mass ratio of 10: (1-2), and placed in an ultrasonic oscillator for oscillation treatment, and then the resulting mixed solution is placed in a vacuum drying oven for drying treatment to obtain uniformly dispersed nano-ceramic powder; the ultrasonic power of the ultrasonic oscillator is 1000-1200 W, and the ultrasonic oscillation time is 8-12 hours; the drying temperature of the vacuum drying oven is 70-90°C, and the drying time is 10-14 hours.
6. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (2), the Al-Si alloy powder has a particle size distribution range of 20-48 μm, a silicon content of 22-55 wt.%, an iron content of 0.08-0.17%, a copper content of 2.3-3.0%, and the remainder being aluminum.
7. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (2), the mixed nano-ceramic powder accounts for 1.5 to 6 wt.% of the mass of the Al-Si alloy powder.
8. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (2), the Al-Si alloy powder and the mixed nano-ceramic powder are uniformly mixed by a QM series planetary ball mill under the protection of an inert gas.
9. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 8, characterized in that: The ball milling adopts the interval type, the rotation speed is 150-250 rpm, the ball milling time is 3-5 h, the ball milling time each time is 14-20 min, and the interval time is 4-6 min.
10. The method for refining primary silicon in Al-Si alloy using nano-ceramic synergistic modification based on laser additive manufacturing according to claim 1, characterized in that: In step (4), the laser power used by the laser powder bed fusion forming equipment is 350-450 W, the scanning speed is 1600-2400 mm / s, the scanning interval is 40-60 μm, the powder thickness is 40-60 μm, and a partitioned island scanning strategy is adopted.
Citation Information
Patent Citations
Preparation method of in-situ synthesized hypereutectic aluminum-silicon alloy alterant
CN104711462A
Carbon nano tubes (CNTs) and graphene nano flakes (GNFs) synergetic enhanced aluminum-based composite and preparation method
CN106399766A
Nano ceramic modified high-silicon aluminum alloy based on selective laser melting
CN111500905A
Nanometer multiphase reinforced aluminum-based composite material and preparation method thereof
CN112974842A
Method for forming aluminum-based amorphous reinforced aluminum-silicon alloy through selective laser melting
CN118616728A
Cited By
Laser powder bed fused heterogeneous multiphase nanoparticle synergistically reinforced aluminum-based alloy and method and application thereof
CN120776170A